THE IMPORTANCE OF INFORMATION TECHNOLOGY IN THE DEVELOPMENT OF THE DIGITAL ECONOMY - Negmatova, N.E. (Educational Research in Universal Sciences, 2023)
The relevance of the article is explained by the fact that today information and communication technologies are an important basis for the development of the economy. The main directions of organizational and economic development during the transition to a post-industrial society were considered in the article. The role of information technologies in the development of the digital economy was revealed, and the measures to increase the rate of economic growth and innovative development of the society through the introduction of information technologies were described. We describe the measures to increase the rate of economic growth and the rate of innovative development of the society based on the introduction of information technologies.